Phantom Indien Episode 1-7 - Malle, Louis; Becker, Etienne (Louis Malle Indien, 2011)
Made with a small crew consisiting of cinematographer Etienne Becker and sound man Jean-Claude Laureux, "Phantom India" is not only a remarkable document of a time and place, but also a meditation on the difficulty of truly knowing the Other. [hcl.harvard.edu]